Solo una scrittura automatica è vera scrittura, cioè poesia (ENTHYMEMA, 2019)
The surrealist movement thought that in the mediumistic technique of automatic writing a way was found to renew art and literature, but the unconscious is not something that can be decided when and how to probe. Writing is a theme dealt with acutely by Jacques Lacan in his last teaching. In this article we will see how, with the assumptions of his research, we can advance the hypothesis that only automatic writing can reach the rank of poetry.
Keywords: automatic writing; spiritism; possession; Jacques Lacan; Real